RETRACTED: Solution of nonlinear Fredholm integro-differential equations using a hybrid of block pulse functions and normalized Bernstein polynomials - Behiry, S.H. (Journal of computational and applied mathematics, 2014)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy). This article has been retracted at the request of the Editor-in-Chief. The Editor-in-Chief of the Journal of Computational and Applied Mathematics has found that the scientific content of “Solution of nonlinear Fredholm integro-differential equations using a hybrid of block pulse functions and normalized Bernstein polynomials” by S.H. Behiry, Journal of Computational and Applied Mathematics, Volume 260 (2014), pages 258–265, was previously published in the journal Abstract and Applied Analysis as “Numerical Solution of Nonlinear Fredholm Integrodifferential Equations by Hybrid of Block-Pulse Functions and Normalized Bernstein Polynomials”, Volume 2013 (2013), Article ID 416757, 8 pages (http://dx.doi.org/10.1155/2013/416757). Double submission and publication of an article represents a serious violation of publishing ethics, and as such this article represents a severe abuse of the scientific publishing system. The Editor-in-Chief of the Journal of Computational and Applied Mathematics, in agreement with the publisher, hereby retract this article and apologize for any inconvenience this may cause.